(untitled) (Journal of Atomic and Molecular Sciences, 2021)
The influence of the isotope substitution on the dynamics of the title reactions is investigated using the quasi-classical trajectory method based on the potential energy surface for the X^1A' ground singlet state of HOBr system. Apparent differences on the stereo-dynamic properties are discovered between the title reactions. These discrepancies are mainly due to the unequal reduced masses of the reactants and different zero-point energies of the transition state, which affect the vector properties of the title reactions.